FTIR Analysis of Nanomodified Cement Concrete Incorporating Nano Silica and Waste Marble Dust. Issue 1 (June 2021) - Singh Kashyap, Vikram; Agrawal, Utkarsh; Arora, Karanpreet; Sancheti, Gaurav
Abstract: In present study, different compositions of concrete mixes with marble dust and nano-silica have been prepared and studied with Fourier Transform Infrared (FTIR) spectroscopy to evaluate different phases formed during hydration reaction. Formation and extent of phases formed during hydration reaction occurring for different curing days can be successfully correlated with the shifting of FTIR bands in various concrete samples. FTIR results demonstrate the shifting in peaks in presence of marble dust and nano-silica as compared to control mix. Decrease in intensity of Raman bands at 1636 and 3400-3650 cm −1 with curing time was observed due to hydration of C3 S and C2 S. The bands observed at 1475 and 890 cm-1 also shift towards lower wave number side 1450-1460 cm −1 with increasing nano-silica content. These peaks are correlated with extent of carbonation which gets decreased in the presence of nano-silica. In addition to this, bands corresponding to ettringite, monosulphate and C-S-H molecules at 1180, 1120 and 980 cm −1 also shift towards lower number side with increase in concentration of nano-silica and marble dust.